2009
DOI: 10.1007/s00005-009-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular glucose transport and glucotransporter 4 expression as a therapeutic target: clinical and experimental studies

Abstract: Introduction: The normalization of cellular glucose assimilation is the basic aim of metabolic therapy in type 2 diabetes mellitus (T2DM). It requires parallel changes in the process of cellular glucose transport (CGT). Therefore the level of CGT could be regarded as a therapeutic target for oral hypoglycemic drugs in T2DM. To explore this hypothesis, CGT levels before and after sulfonylurea therapy were investigated. Peripheral blood lymphocytes were used as a cell model for testing CGT. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…PBMCs are increasingly used as a surrogate model for glucose disposal. Recent studies have shown that PBMCs have insulin-sensitive GLUT4 activity and that GLUT4 increases on the membrane of monocytes [ 33 , 34 , 35 ] and lymphocytes [ 36 , 37 ] in response to insulin. Furthermore, we previously reported alterations of the insulin signaling cascade in PBMCs from obese individuals [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…PBMCs are increasingly used as a surrogate model for glucose disposal. Recent studies have shown that PBMCs have insulin-sensitive GLUT4 activity and that GLUT4 increases on the membrane of monocytes [ 33 , 34 , 35 ] and lymphocytes [ 36 , 37 ] in response to insulin. Furthermore, we previously reported alterations of the insulin signaling cascade in PBMCs from obese individuals [ 29 ].…”
Section: Introductionmentioning
confidence: 99%